The history and viability of constitutivism in ethics - Roberts, A; Regent, M (2019)
The topic of this thesis is constitutivism in ethics: its history and its viability. Constitutivists hope to show that moral standards are normative because if we are not following them, we are failing to be agents. We cannot escape trying to be agents: it is just our way of trying to do anything in particular. In failing to be agents, then, we are failing to do what we ourselves are trying to. The force of normativity, on a constitutivist view, turns out to be the force of our own efforts to do things. Moral or pro-moral standards are what we must be guided by for our own attempts to do things to be internally consistent. The immoral would-be agent, then, is one who is divided against themself. They are trying to do the impossible: to be agents in a way that agents cannot. Defending the viability of constitutivism – one half of my topic – only takes defending one form of it. This thesis focuses on Kantian constitutivism, which may be the most promising kind of it. It focuses in particular on Christine Korsgaard’s version of that position, as presented in The Sources of Normativity, Self-Constitution, her recent Fellow Creatures, and a range of essays. The four substantive chapters of this thesis set out to answer four different questions. The first is what the components of Kantian constitutivism are. Two of those four components are claimed to be characteristic of constitutivism in ethics, and the chapter points to the historical background of all four of them. The second question is in what sense we face the problem of agency. The chapter first distinguishes rational and nonrational agency. It then explains how, on the view, rationality is self-conceptual, and attempts to pin down this talk of problem-facing. The final two chapters of this thesis take up two closely related questions. These are why our moral psychology should feature what Kant calls “incentives,” and why, as Kant and Aristotle believe, it should feature not just acts, but ends. It argues that on the Kantian constitutivist picture, there are two demands on a moral philosophy of action. Those demands can be seen to generate the functional concepts of incentives and, via the steps of a Kantian moral argument, ends.